Intelligence unbound : the future of uploaded and machine minds - Blackford, Russell, 1954-; Broderick, Damien (Chichester, West Sussex, UK : Wiley Blackwell, 2014)
Intelligence Unbound explores the prospects, promises, and potential dangers of machine intelligence and uploaded minds in a collection of state-of-the-art essays from internationally recognized philosophers, AI researchers, science fiction authors, and theorists. -Compelling and intellectually sophisticatedexploration of the latest thinking on Artificial Intelligence and machine minds -Features contributions from an international cast of philosophers, Artificial Intelligence researchers, science fiction authors, and more -Offers current, diverse perspectives on machine intelligence and uploaded minds, emerging topics of tremendous interest -Illuminates the nature and ethics of tomorrow's machine minds'and of the convergence of humans and machines'to consider the pros and cons of a variety of intriguing possibilities -Considers classic philosophical puzzles as well as the latest topics debated by scholars -Covers a wide range of viewpoints and arguments regarding the prospects of uploading and machine intelligence, including proponents and skeptics, pros and cons.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Artificial intelligence -- Forecasting; Thought and thinking; COMPUTERS / General; Künstliche Intelligenz; Philosophy; Electronic books; Electronic books